2020
DOI: 10.1155/2020/3074313
|View full text |Cite
|
Sign up to set email alerts
|

Urinary I-FABP, L-FABP, TFF-3, and SAA Can Diagnose and Predict the Disease Course in Necrotizing Enterocolitis at the Early Stage of Disease

Abstract: Necrotizing enterocolitis (NEC) is a severe gastrointestinal disease affecting mainly preterm newborns. It is characterized by unexpected onset and rapid progression with specific diagnostic signs as pneumatosis intestinalis or gas in the portal vein appearing later in the course of the disease. Therefore, we analyzed diagnostic and prognostic potential of the markers of early NEC pathogenesis, such as excessive inflammatory response (serum amyloid A (SAA)) and gut epithelium damage (intestinal and liver fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
0
31
1
6
Order By: Relevance
“…Contrary to our previous findings, Doi et al reported an association between urinary L-FABP and 14-day mortality, in addition to the onset of AKI [5]. L-FABP was originally discovered as a specific marker for AKI; however, in recent years, it has been reported that urinary L-FABP increases due to damage to various other organs or surgical invasion [6][7][8][9][10][11][12][13][14], and therefore, it has also emerged as a marker of general organ damage.…”
Section: Introductioncontrasting
confidence: 93%
“…Contrary to our previous findings, Doi et al reported an association between urinary L-FABP and 14-day mortality, in addition to the onset of AKI [5]. L-FABP was originally discovered as a specific marker for AKI; however, in recent years, it has been reported that urinary L-FABP increases due to damage to various other organs or surgical invasion [6][7][8][9][10][11][12][13][14], and therefore, it has also emerged as a marker of general organ damage.…”
Section: Introductioncontrasting
confidence: 93%
“…I-FABP is an intracellular protein specifically and abundantly expressed in intestinal epithelial cells, and its increased serum concentration represents intestinal epithelial cell damage and IB dysfunction ( Gajda & Storch, 2015 ; Wells et al, 2017 ). As a biomarker of IB dysfunction, I-FABP determination has been used in patients with necrotizing enterocolitis ( Coufal et al, 2020 ), acute mesenteric ischemia ( Salim et al, 2017 ), strangulated small bowel obstruction ( Kittaka et al, 2014 ), Crohn’s disease ( Sarikaya et al, 2015 ), blunt trauma ( Matsumoto et al, 2017 ), celiac disease ( Oldenburger et al, 2018 ), acute pancreatitis( Kupcinskas et al, 2018 ; Goswami et al, 2017 ), acute decompensated heart failure ( Kitai et al, 2017 ), chronic renal failure ( Okada et al, 2018 ), septic shock ( Sekino et al, 2017 ), psoriasis ( Sikora et al, 2019 ), and even physiological stressor-induced intestinal damage ( March et al, 2017 ). In addition to serum I-FABP, many other biomarkers are used to measure IB function ( Wells et al, 2017 ; Piton & Capellier, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For critically ill children, where the body is in a stressed state, serum ITF concentration is associated with gastrointestinal failure and prognosis[ 20 ]. Another study has suggested that urinary ITF can help diagnose and predict the disease course in necrotizing enterocolitis at the early stage in newborns[ 21 ]. Previous studies have also paid close attention to the application of ITF to inflammatory bowel disease, showing that ITF could be used as a biomarker to predict disease activity and assess mucosal healing in ulcerative colitis[ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%